2018
DOI: 10.1007/978-1-4939-8567-8_15
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo ELISpot Assay to Investigate Dengue Virus Specific T-Cell Responses

Abstract: Enzyme-Linked ImmunoSpot (ELISpot) assay is a functional T cell assay which is commonly used to assess virus-specific T cell responses. We have used ex vivo ELISpot responses to investigate the role of dengue virus (DENV) specific T cells in acute dengue infection, to evaluate their role in possible disease pathogenesis and protection. We have also used ex vivo IFNγ ELISpot assays to determine the functionality of T cell responses in those who were previously naturally infected with dengue and we have determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…DENV‐NS3 peptide array is comprised of 105, 14‐ to 17‐mer peptides while NS5 proteins were consisted of 156 peptides. The peptides were reconstituted as previously reported . DENV‐NS3 and ‐NS5 peptides were pooled separately to represent the DENV‐NS3 and ‐NS5 proteins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DENV‐NS3 peptide array is comprised of 105, 14‐ to 17‐mer peptides while NS5 proteins were consisted of 156 peptides. The peptides were reconstituted as previously reported . DENV‐NS3 and ‐NS5 peptides were pooled separately to represent the DENV‐NS3 and ‐NS5 proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The peptides were reconstituted as previously reported. 24 DENV-NS3 and -NS5 peptides were pooled separately to represent the DENV-NS3 and -NS5 proteins. Final concentration of dimethyl sulfoxide is less than 0.5%.…”
Section: Peptidesmentioning
confidence: 99%
“…Ex vivo ELISpot assays were performed as previously described [see detailed description under cultured ELISpot assays (14,31,32)]. In ex vivo ELISpot assays PBMCs 1 × 10 5 were added to each well and JEV-specific, conserved peptides were added at a final concentration of 10 µM as previously described and tested in duplicate (32) The spots were enumerated using an automated ELISpot reader (AID, Germany).…”
Section: Ex Vivo Elispot Assaysmentioning
confidence: 99%
“…Another study showed that ILC produce higher IL-4/IL-13 or GATA3+ in dengue infection with warning signs compared to dengue infection without warning signs 32 . Additionally, dengue patients who had lower DENV-NS3 specific IFN-γ production by T cells since the onset of illness, before development of ‘critical phase’, were significantly likely to subsequently develop DHF 33 , 34 . Also, lung ILC2 from mice challenged with H1N1 virus subtype, containing a functional PB1-F2 virulence factor, induced a dominant IL-13 + CD8 T cell response, regardless of host IFN-γ expression 35 .…”
Section: Introductionmentioning
confidence: 99%